The Determinant Factors of Intention to Use Cloth Diapers in The Yogyakarta Area - Reni Dwi Astuti; Wandhansari Sekar Jatiningrum (OPSI, 2023)
To anticipate environmental damage, one of the efforts is to use green products, including cloth diapers which are more environmentally friendly because they can be used repeatedly, thus reducing the waste of disposable diapers. For this reason, a study was conducted to determine the factors influencing the purchasing intention of environmentally friendly diapers. The factors studied included attitudes, subjective norms (SN), perceptions of behavioral control (PBC), environmental awareness (PL), moral responsibility (Norm), and perceived risk (PR). These six factors will be tested to determine whether they significantly influence the intention to use cloth diapers, then their effect will be analyzed. The objects in this study are residents of the City of Yogyakarta who have and take care of infants or toddlers. Data was obtained by distributing questionnaires. Data processing begins with validity and reliability testing. After testing the validity and reliability, it is followed by regression tests, model significance, significance test for the influence of each independent variable, and finally, determining the coefficient of determination. From the processing of the 406 questionnaires, it is known that three variables significantly influence: subjective norms, perceptions of behavioral control, and moral responsibility. The resulting regression equation is Intention=0.045attitude+0.288 SN+0.277PBC+0.009PL-0.020PR+0.316Norm. The coefficient of determination of the conceptual model is 64.2%, which means that changes in the values of the six variables studied contribute to a variation in the response variable (intention) of 64.2%.